Preharvest treatment with 1-aminoethoxyvinylglycine and gibberellin on the quality and physiology of cashew peduncles - Souza, Kellina Oliveira; Xavier, Cícera Vanuza; Lopes, Mônica Maria de Almeida; Moura, Carlos Farley Herbster; Silva, Ebenezer Oliveira; Ayala-Zavala, Jesus Fernando; de Miranda, Maria Raquel Alcântara (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effects of the preharvest treatment with gibberellic acid (GA3) and aminoethoxyvinylglycine (AVG) on the quality and physiological attributes of ripe 'CCP 76' cashew (Anacardium occidentale) peduncles at different developmental stages. Sprays of 180 mg L-1 GA3 and 180 mg L-1 AVG were applied, combined and isolated, at 34, 40, and 44 days after anthesis (DAA), and peduncles were harvested ripe at 46 DAA and evaluated for physical and physiological variables. The treatment with GA3 resulted in firmer peduncles with a greater apical diameter, but did not affect the physiological variables activity of the pectin methylesterase and polygalacturonase cell wall enzymes and degree of lipid peroxidation of the biological membranes, nor the physical attributes total mass (peduncles and nut) and nut size. At early developmental stages (34 DAA), GA3 increased the activity of the antioxidant enzymes superoxide dismutase and catalase, and, at later stages (40 DAA), promoted polyphenol and carotenoid accumulation. The application of AVG at the final stages (44 DAA) provided greater total antioxidant activity, despite the lower ascorbate peroxidase activity. The application of GA3 pre-harvest increases the firmness and diameter of the cashew peduncles, and the treatment with AVG increases the total antioxidant activity of the peduncles.